Analisis Perkembangan Penelitian Living Al-Qur'an dan Hadis - Wahyudin Darmalaksana; Neli Alawiah; Elly Hafifah Thoyib; Siti Sadi'ah; Ecep Ismail (UIN Sunan Gunung Djati Bandung, 2019)
Research on â€œliving Al-Qur'an and hadithâ€ seems to experience rapid development based on the spirit of integration of science between Islamic science and general science. This study aims to discuss the main aspects in the development of the study â€œliving Al-Qur'an and hadith.â€ This research is qualitative in nature using the literature study method and content analysis approach. The results of this study indicate that the main aspects of the study â€œliving Al-Qur'an and hadithâ€ include the theoretical foundation, research methodology, and analysis. As a discussion of this research is that various variants in the conduct of research has produced a variety of research models â€œliving Al-Qur'an and hadith.â€ These models are treasures of knowledge in the development of research â€œliving Al-Qur'an and hadithâ€ in Indonesia.